Digital Transformation in the Innovation Process: Implications for the Growth of Startups and MSMEs in the Digital Economy Era (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
Digital transformation has revolutionized the innovation process in organizations, particularly in startups and MSME, which are the backbone of Indonesia's economy. The integration of technologies such as cloud computing, artificial intelligence, and digital platforms opens up enormous opportunities to create new adaptive products and business models, accelerate responses to market needs, and improve operational efficiency. This study aims to examine how digital transformation affects the innovation process and its implications for the growth of startups and MSMEs in the rapidly changing digital economy. Using a descriptive qualitative method, the study identifies the drivers and barriers to the adoption of digital transformation in innovation in both business segments. The results show that digitalization drives business growth through more responsive and scalable innovation, despite significant challenges related to digital literacy, infrastructure, and policy support. This study provides strategic recommendations to strengthen the digital innovation ecosystem in the startup and SME sectors.
Keywords: digital transformation; innovation, startups; MSME; digital economy